Blood flow energy loss: a predictor for the recovery of left ventricular function after bioprosthetic aortic valve replacement. (8th May 2021) - Hohri, Yu; Itatani, Keiichi; Numata, Satoshi; Yamazaki, Sachiko; Miyazaki, Shohei; Nishino, Teruyasu; Yaku, Hitoshi
Abstract: : OBJECTIVES: It is difficult to estimate the improvement in left ventricular (LV) function after aortic valve replacement (AVR). The present study aimed to evaluate whether energy loss (EL) can predict the postoperative LV function after AVR. METHODS: Nine patients who underwent AVR with a bioprosthetic valve were enrolled in the present study. Porcine prostheses were used in 5 patients and bovine pericardial prostheses were used in 4 patients. The aortic flow pattern was visualized and EL and cardiac output (CO) were measured using 4-dimensional flow magnetic resonance imaging from the LV to the descending aorta; the EL/CO ratio in the extracted area was calculated as total EL/CO ratio. RESULTS: With a porcine valve, a severe helical flow was observed in the ascending aorta during the holosystolic phase. In contrast, with a bovine pericardial valve, straight transvalvular aortic flow was observed in the early systolic phase and 2 large vortical flows occurred on both sides of the greater and lesser curvature of the ascending aorta after the mid-systolic period. The total EL/CO ratio was strongly correlated with LV ejection fraction improvement after AVR ( r = 0.74, P = 0.02). CONCLUSIONS: The aortic flow pattern is different between the porcine valve and bovine pericardial valve. The total EL/CO ratio is a valuable tool for evaluating the postoperative LV ejection fraction improvement after AVR. Optimization of total EL/CO ratio would have potential to improve haemodynamic performances after AVR.